Admission Glucose Levels May Increase the Risk for Early Neurological Deterioration in Females With Acute Ischemic Stroke - Huang, Zhi-Xin; Huang, Yan; Zeng, Jie; Hao, Hong; Petroski, Greg F.; Lu, Haike; Liu, Xintong; Liu, Zhenguo (Frontiers in Neurology, 2020)
Background and purpose: Early neurological deterioration (END) is associated with poor outcome for patients with acute ischemic stroke (AIS). Patients with hyperglycemia have increased risk for stroke and tend to have poor outcome with and without diabetes after stroke. The present study aimed to determine if blood glucose was associated with END and if sex difference was present in the development of END in AIS patients. Methods: A total of 220 consecutive patients (both males and females) with AIS between 2012 and 2015 were screened for this retrospective study. After exclusion, 213 patients were included for analysis. Propensity-score matching was used for normalization of variables including stroke severity, time from symptom onset to treatment, and treatment methods. Results: END was present in 68 patients (31.9%). Multivariate regression analysis showed that the risk of END was significantly higher in males with AIS than in females (P < 0.001), and admission blood glucose level was independently associated with END (P < 0.001). However, subgroup analysis demonstrated that admission glucose levels were significantly associated with increased risk for END only in females, but not in males (P = 0.008). When the cutoff value of 107.1 mg/dL was used, the admission blood glucose level had a significant predictive value for END prediction with a sensitivity of 100% and a specificity of 53% in female patients. Conclusions: The data demonstrated that sex difference was present for the development of END in AIS patients with an increased risk for males. The present study also showed that admission glucose level could be an important predicting factor for END in female patients with AIS.